(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the effects of P2X7 receptor inhibition by Brilliant Blue G dye (BBG) in an experimental mode of pulmonary paracoccidioidomycosis. Methodology: Thirty male rats were divided into five groups: absolute control group, negative control group, experimental group 50, experimental group 100, and experimental group 150. The last four groups underwent experimental induction of pulmonary paracoccidioidomycosis; however, only the brilliant blue G experimental groups 50, 100, and 150 were administered BBG intraperitoneally every 48 h at doses of 50, 100, and 150 mg/kg respectively, to inhibit P2X7 receptor activity. To assess the effects of this treatment, lung tissue was analyzed histologically and the levels of the anti-gp43 antibody were measured by enzyme-linked immunosorbent assay. Results and conclusion: Lung biopsies of the animals treated with BBG exhibited a significant reduction in the number and area of granulomas with lower levels of anti-gp43 antibodies relative to those in the untreated group. Treatment with BBG reduced the number and area of granulomas in the lung tissue and levels of anti-gp43 antibodies against Paracoccidioides brasiliensis, thereby mitigating pulmonary paracoccidioidomycosis in the experimental model.